In Support of an Alternative Model of Two-Dimensional Line Drawing Interpretations of Partially Occluded Patterns - Embong, Abdullah (Malaysian Journal of Computer Science, 1996)
This paper presents some experimental findings in support of a proposed model of two-dimensional line drawing interpretations of partially occluded patterns based on local and global minima. It describes the phenomena of partial occlusion and considers two types of interpretations: mosaic and completion. Some critiques of global minimum principle are discussed and an alternative approach is suggested. Perceptual preference based on the proposed model is tested on selected patterns and the discussion on the results is then presented. Some future works are also suggested.